BIOCHEMICAL CHARACTERISTICS OF THIONIC FLUVISOL LINKED TO LAND USE TYPES IN SOUTHERN VIETNAM - Nguyen Tan Chung; Sy Danh Chung; Hoang Van Thoi (SEAMEO BIOTROP, 2017)
Thionic Fluvisols soil in Southern Vietnam is like typical acid sulfate soil in the tropics and is severely polluted due to human activities. Salinity intrusion and industrial wastewater contamination are the main causes of environmental degradation in the soil ecosystem. This research aimed to determine a link between biochemical soil properties and land use types to provide suitable solutions for afforestation and soil restoration. Soil sampling was conducted in five different land use types at four soil layers (O, AB, Bj, and Cp). The five land use types were sugarcane crop; Melaleuca plantation; 2-year Acacia plantation; 5-year Acacia plantation; and control (grass-covered land). The results showed that soil in those five land use types was very acidic (pH ≤ 4) with poor nutrient conditions, with orthophosphate content ranging from 378–640 mg/kg, N-NH₄ from 586–999 mg/kg, and N-NO₃ from 830–1,112 mg/kg. Concentrations of toxic ions were very high, with large variation among land use types and soil depths: 1,799–12,403 mg SO₄²⁻/kg; 22–1,645 mg exchangeable Fe/kg; and 34–88 mg Al/kg soil. The lowest concentrations of exchangeable Fe²⁺ and SO₄²⁻ ions were found in sugarcane and Melaleuca plantations, respectively. Twenty-three sulfur-oxidizing bacteria and two iron-oxidizing bacteria were identified. All these bacteria were initially identified as Thiobacillus sp. Sugarcane and Melaleuca plantations exhibited the most diverse Thiobacillus species, which was linked to the reduction of exchangeable Fe²⁺ and SO₄²⁻ concentrations in these two land use types. This study indicated that Thiobacillus sp. could grow well in the Thionic Fluvisols. It is proposed that Melaleuca and sugarcane species could reduce iron and sulfur contents in Thionic Fluvisols in the tropics.